2014
DOI: 10.1111/pcmr.12254
|View full text |Cite
|
Sign up to set email alerts
|

Degree of polymerization of 5,6‐dihydroxyindole‐derived eumelanin from chemical degradation study

Abstract: Eumelanin is a brown-black pigment comprising 5,6-dihydroxyindole (DHI) and its 2-carboxy derivative (DHICA), but the detailed structure of eumelanin is unclear. Chemical degradation is a powerful tool for analyzing melanin. H2 O2 oxidation degradation of eumelanin affords pyrrole-2,3,5-tricarboxylic acid (PTCA) and pyrrole-2,3-dicarboxylic acid (PDCA). The ratio of PDCA to PTCA provides information about the eumelanin structure. In this article, we propose simple equations on the basis of previous experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…It must be considered, however, that these studies only analyzed eumelanin degradation products and did not include unaltered eumelanin like in this study. It must also be considered that our model predicted DHICA contents in synthetic eumelanins slightly higher than real values (Table ), which may be due to the fact that some DHICA units are decarboxylated during the polymerization to DHI units (Okuda et al., ). Our results thus indicate that the analysis of unaltered eumelanins by Raman spectroscopy can provide new insights into the structure of eumelanin and suggest that the DHI:DHICA ratio may be highly variable among natural eumelanins.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…It must be considered, however, that these studies only analyzed eumelanin degradation products and did not include unaltered eumelanin like in this study. It must also be considered that our model predicted DHICA contents in synthetic eumelanins slightly higher than real values (Table ), which may be due to the fact that some DHICA units are decarboxylated during the polymerization to DHI units (Okuda et al., ). Our results thus indicate that the analysis of unaltered eumelanins by Raman spectroscopy can provide new insights into the structure of eumelanin and suggest that the DHI:DHICA ratio may be highly variable among natural eumelanins.…”
Section: Discussionmentioning
confidence: 82%
“…Eumelanins were prepared by adding 2 ml of a solution of mushroom tyrosinase (Sigma‐Aldrich; 4,270 U/mg) in 0.1 M sodium phosphate buffer (pH 6.8) to a solution of 1 mmol of either DHI, DHICA or a 50:50, 25:75 or 75:25 mixture of DHI and DHICA in the same buffer (Ito, Wakamatsu, Glass, & Simon, ; Okuda, Yoshino, Wakamatsu, Ito, & Sota, ; Ozeki, Wakamatsu, Ito, & Ishiguro, ). Oxidation was induced by vigorous stirring during 4 hr at 25°C, and then stopped by adding 6 M HCl.…”
Section: Methodsmentioning
confidence: 99%
“…Another possible explanation for the increase of the carboxylic group when oxygen pressure is used during synthesis is the formation of pyrrole-2,3-dicarboxylic acid (PDCA) and pyrrole-2,3,5-tricarboxylic acid (PTCA) from melanin degradation due to nucleophilic attack of OOH − ions. 34,[36][37][38][39] Nonetheless, it is expected that this process occurs only at high concentrations of H 2 O 2 , as in some bleaching experiments. 34 Thus, we believe that the amount of H 2 O 2 formed during our procedure will not be enough to induce catechol ring fission.…”
Section: Discussionmentioning
confidence: 99%
“…This variety of oligomers and redox forms that constitute PDA and eumelanin is referred to as chemical disorder model. 32 …”
Section: Introductionmentioning
confidence: 99%
“…18–22 A recent study based on mass spectroscopy results of DHI-melanin also suggested that the majority constituents of the material are tetramers and pentamers of DHI. 32 Consequently, we narrow down our investigation to DHI oligomers up to tetramers. Within the framework of this bottom-up approach and considering the location of the most reactive positions of DHI, we systematically generate and analyze all probable early-polymerized DHI oligomers, ranging from dimers to tetramers, to provide a fundamental explanation of some important structural features of PDA and eumelanin, as well as to propose a set of molecular models that represents the chemically diverse nature of these materials.…”
Section: Introductionmentioning
confidence: 99%